The "Polluter Pays" Principle Applied to Micro, Small and Medium Enterprises in Ecuador, is it Efficient? - Cornejo Ramón, Jose Gabriel; Cárdenas Cifuentes, Manuela (Iuris Dictio, 2021)
One of the foundations of environmental law is the well-known "polluter pays" principle. In the national legal system, this principle is favored by the Constitution (given its biocentric conception of law), also recognized in the Código Orgánico del Ambiente, and developed by rules of inferior hierarchy. This research examines the purpose of this principle, and its incorporation into national legislation. Additionally, it determines what is meant by micro, small and medium-sized enterprises (MSME"™s). The objective of the article is to analyze the convenience of applying the "polluter pays" principle to MSME"™s in Ecuador. These have been affected by the application of this principle due to the lack of economic and technical resources that characterizes them, thus generating a problem both for these companies and for the effectiveness of the norm. To this end, a general analysis of the situation of these companies in Ecuador will be carried out, as well as their position in relation to the requirements of Ecuadorian environmental legislation and the applicability of the "polluter pays" principle.